PEMBINAAN SENI BACA ALQURAN PADA ANAK-ANAK DI DESA LUMBAN PASIR - Suryadi Nasution; Mhd. Yusri Nasution (Prodi Pendidikan Agama Islam STAIN Mandailing Natal, 2020)
The aim of this Study is to know the process of developing teaching learning of holy Qur’an in Lumban Pasir Village. This research used Qualitative approach by using 3 Instruments, namely, Interview, observation and documentation. The Results of the study show that student’s interest and talents for reciting Holy Qur’an are more focused than before. It is happening because the activities plan work consistently. In developing teaching of Holy Qur’an, there are several generations applied various religious activities such as adzan and following MTQ Competitions at various levels.